Remarks on the age and growth of the squid Illex illecebrosus (le suer, 1821) - Maxim, Cornelia; Lazu, Dorel (Cercetări Marine - Recherches Marines, 2026)
This paper presents observations concerning the age and growth of the squid Illex caught in July-August 1979 in the Northwest Atlantic. There are calculated some elements of correlation between the hypothetic age of the squid, length of mantle and statolith, by length and sex classes.